2017
DOI: 10.1038/s41598-017-11568-4
|View full text |Cite
|
Sign up to set email alerts
|

A unique case of human Zika virus infection in association with severe liver injury and coagulation disorders

Abstract: AbsatrctZika virus (ZIKV) has caused major concern globally due to its rapid dissemination and close association with microcephaly in children and Gullian-Barr syndrome in adults. In this study, we identified a patient returned from Cambodia who experienced high fever, chill and myalgia. Lab tests discovered sign of severe liver injury including significantly elevated serum transaminases’ level, decreased serum albumin level, and markedly increased levels of lactic dehydrogenase, alpha-hydroxybutyric dehydroge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 25 publications
2
32
0
Order By: Relevance
“…Furthermore, there was a case reported in 2017 that a patient with human Zika virus infection had markedly elevated LDH, which was associated with 70% mortality in further a Zika-infected animal study. They considered LDH as an indicator of multiorgan injury, not only affecting liver or cardiac function [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, there was a case reported in 2017 that a patient with human Zika virus infection had markedly elevated LDH, which was associated with 70% mortality in further a Zika-infected animal study. They considered LDH as an indicator of multiorgan injury, not only affecting liver or cardiac function [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…preprint (which was not certified by peer review) is the author/funder, who has granted medRxiv a license to display the preprint in further Zika infected animal study. They considered LDH as an indicator of multiorgan injury, not only affecting liver or cardiac function (15).…”
Section: Discussionmentioning
confidence: 99%
“…Others have shown that serum ALT is elevated following ZIKV infection [ 63 , 64 , 66 , 71 ], in both rhesus and cynomolgus macaques as well as following DENV-2 infections in African green monkeys ( Chlorocebus aethiops ) [ 84 ]. Human disease does not necessarily present with elevated ALT levels but can in cases be associated with hepatic disease and coagulopathy [ 85 ].…”
Section: Discussionmentioning
confidence: 99%